A study of etiological and clinical profile of patients with severe anemia in a tertiary care hospital - P., Dasharatham; Reddy, V. Samyuktha (International Journal of Advances in Medicine, 2018)
Background: Though anemia due to iron deficiency is quite common in India there has been little wok done on the incidence of etiopathogenesis of severe anemia without apparent cause. Anemia is prevalent throughout the world. The objective of the present endeavour was to study the prevalence of severe anemia, to form an etiological categorization of anemia and to study the prevalence of heart failure in the study group Methods: Total of 50 patients admitted to the medical ward of MediCiti Institute of Medical Sciences and meeting all the exclusion and inclusion criterion were studied. All the patients were subjected to a detailed history and physical examination. All cases were examined in detail according to proforma, investigations, pathological examination and other special tests were carried out. Results: Female preponderance in a ratio of 3:2 was seen. Nutritional anemia was the most common etiology and all cases were seen only in females. Fatigue and tiredness were reported by all patients, hepatomegaly was the most in 42% of the patients. 38 (76%) were found to have cardiac murmurs. As the hemoglobin increased the proportion of patients with heart failure reduced. But this trend was not found to be statistically significant. The association between Hb level and presence of hepatomegaly or splenomegaly was not found to be statistically significant. Thrombocytopenia was the most common cytopenia found in 34%. Only 16% of the patients with severe anemia were found to have normocytic normochromic picture. Conclusions: Severe anemia was found to be associated with morbidity. Hence early detection and prevention by vigorous treatment is important.